The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1021/acscatal.6b01204
|View full text |Cite
|
Sign up to set email alerts
|

EPR Study of Substrate Binding to Mn(II) in Hydroxynitrile Lyase from Granulicella tundricola

Abstract: GtHNL from Granulicella tundricola is a Mn­(II) containing hydroxynitrile lyase with a cupin fold. The quasi-octahedral manganese is pentacoordinated by the enzyme. It catalyzes the enantioselective addition of HCN to aldehydes, yielding R-cyanohydrins. On the Lewis acidic vacant coordination site the Mn binds either substrate or the product, leading to a hexacoordinated 17 electron complex. EPR spectra of the active enzyme are unusually wide with a zero-field splitting approximately equal to the X-band microw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…These results are of particular interest, since solvated Mg 2+ and Mn 2+ ions are known to be poor Lewis acid catalysts in aqueous media . A previous study on the Mn 2+ containing enzyme Gt HNL suggested a distorted octahedral coordination geometry to be responsible for the increased Lewis acidity, where the connecting line between the two tops of the square‐based pyramid deviates from the expected angle of 180° . A similar deviation was also observed in the crystal structure of holo‐ Sw HKA for the Mg 2+ cluster (6r62.pdb).…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…These results are of particular interest, since solvated Mg 2+ and Mn 2+ ions are known to be poor Lewis acid catalysts in aqueous media . A previous study on the Mn 2+ containing enzyme Gt HNL suggested a distorted octahedral coordination geometry to be responsible for the increased Lewis acidity, where the connecting line between the two tops of the square‐based pyramid deviates from the expected angle of 180° . A similar deviation was also observed in the crystal structure of holo‐ Sw HKA for the Mg 2+ cluster (6r62.pdb).…”
Section: Resultssupporting
confidence: 64%
“…A similar change in the zero‐field splitting has previously been reported for the Mn(II) bound extradiol cleaving catechol dioxygenase upon the addition of the substrate 3,4‐dihydroxyphenylacetate and for Mn(II) bound pyruvate kinase upon the addition of pyruvate or phosphoenolpyruvate . Spectra similar to the pyruvate bound Mn‐ Sw HKA have also been reported for oxalate decarboxylase, oxalate oxidase, hydroxynitrile lyase Gt HNL and phosphoglucosemutase …”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…H8A mutant was completely inactive, whereas Y30F mutant exhibited a low activity (~ 5% of wild‐type). Thus, His8 is essential for the reaction and acts as a general base to deprotonate the hydroxyl group in Pe HNL as observed in other HNLs []. The mutants of Asn101 (N101A and N101D) were completely inactive.…”
Section: Resultsmentioning
confidence: 99%
“…HNLs include diverse groups of enzymes belonging to various protein families. Six unrelated structural classes of HNLs have been reported so far; glucose‐methanol‐choline oxidoreductase , α/β‐hydrolase , carboxypeptidase , zinc‐dependent alcohol dehydrogenase , cupin superfamily , and recently solved Bet v1 superfamily . Although these HNLs react with similar or identical substrates, the architectures of their active sites are largely different.…”
Section: Introductionmentioning
confidence: 99%